2023
DOI: 10.1029/2022jb025153
|View full text |Cite
|
Sign up to set email alerts
|

Data Assimilation Using High‐Frequency Radar for Tsunami Early Warning: A Case Study of the 2022 Tonga Volcanic Tsunami

Abstract: Tsunami early warning based on the data assimilation (DA) approach is a recent technique (Maeda et al., 2015). It directly uses offshore observations to reconstruct the tsunami wavefield and does not require tsunami source information for forecasting. Therefore, it is applicable to tsunamis generated by various sources, such as earthquakes, landslides, and volcanic eruptions (Gusman et al., 2016;. Offshore tsunami observations are primarily provided by offshore bottom pressure gauges (OBPGs). They measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 49 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…The improved kernel principal component analysis method is selected to reduce the dimensions of the debris-flow prediction index data so as to avoid the problem of dimension disaster during debris-flow prediction. The support vector machine is used to predict debris flow [21]. Through experimental verification, this method can accurately predict debris flows, and the error between the predicted results and the actual results is less than 5%, improving the accuracy of debris-flow prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The improved kernel principal component analysis method is selected to reduce the dimensions of the debris-flow prediction index data so as to avoid the problem of dimension disaster during debris-flow prediction. The support vector machine is used to predict debris flow [21]. Through experimental verification, this method can accurately predict debris flows, and the error between the predicted results and the actual results is less than 5%, improving the accuracy of debris-flow prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of studies such as this include (1) the local nature of the data, limited with respect to space and time (satellite data, for example, can provide much more extensive data with respect to geographical and temporal reach); (2) the video footage is subjective to some degree, dependent on what caught the eye of the video-maker at the time of its filming-this aspect can be mitigated using numerous videos and judicious selection in the videos chosen for detailed analysis; (3) estimates of parameters such as flow velocity are undertaken in a relatively low-technology and highly practical manner, although results from this study are comparable with other studies as demonstrated above. There are techniques, such as discussed in [34] with respect to radar techniques, for flow rate calculations that have a higher level of sophistication than techniques applied in this study. We propose, however, that studies such as ours have significance from the point of view of (1) utilisation of widely available data generated by the 'general public' with a geoscience and geohazard lens, and analysis by geoscience experts; (2) the richness of the data for local urban and rural environments; (3) the deployment of novel analytical techniques that enhance and improve research focus, such as the interactive object orientation imagery technique (other GIS and ICT techniques will become increasingly more available and sophisticated with time); (4) the development of systematic and consistent methods and approaches to video analysis and open transparent accounts of these, as present in this study; and (5) the addition of 'research depth' and practical application to the results.…”
Section: Further Analysis: Research Significance Limitations Tsunami ...mentioning
confidence: 99%